Política industrial e desenvolvimento econômico no Brasil : uma discussão sob a ótica Kaleckiana - Messias, Viviane Mota (2014)
The opening trade and the liberalizing measures initiated in the end of 1980s created the need to modify the productive structure of the brazilian economy, so far, not prepared for this process. It was necessary to increase competitiveness, particularly by strengthening industry. This context was compatible with the Theory of Economic Development of Michal Kalecki, who proposed that the development would be directly related to the investments and the implementation of innovative ways to boost the industry. Following this perspective, appear to be essential to adopt an industrial policy that promotes the competitiveness of the economy, paving the way for sustainable economic development. However, due to mismatches in the 1980s and 1990s, the developmental practices were put in the background, turning part of political discussions in Brazil in 2004. Accordingly, this thesis conducted a reflective discussion of recent Brazilian industrial policy, seeking to understand whether and to what extent this policy has fulfilled the role of enhancing the competitiveness of the economy, and thus substantiate the development process. After about ten years of the adoption of a declared industrial policy aimed at promoting innovation, the results of this sector proved to be very insignificant, proving that industrial policy has not been effective in its purpose. The economic growth and development in Kaleckian molds are occurring so contained, since the investment and innovation efforts are still not sufficient to increase the share of high technology products in industrial performance in 2012 showed that its smaller contribution to the national product in over sixty-five years. Despite all efforts, industrial performance has been dominated by low and medium technology goods, which are more fragile. The policy has proven crucial for creating productive and innovative bases, but after a decade of implementation, it´s not possible to say that it was successful in its goal of achieving economic growth and improving the country's performance in foreign markets by promoting high-tech industry.